Ultralarge von Willebrand factor fibers mediate luminal staphylococcus aureus adhesion to an intact endothelial cell layer under shear stress - Pappelbaum, Karin; Gorzelanny, Christian; Grässle, Sandra; Suckau, Jan; Laschke, Matthias W.; Bischoff, Markus; Bauer, Corinne; Schorpp-Kistner, Marina; Weidenmaier, Christopher; Schneppenheim, Reinhard; Obser, Tobias; Sinha, Bhanu; et al. (Circulation, 2013)
Background— - - During pathogenesis of infective endocarditis, Staphylococcus aureus adherence often occurs without identifiable preexisting heart disease. However, molecular mechanisms mediating initial bacterial adhesion to morphologically intact endocardium are largely unknown. - - Methods and Results— - - Perfusion of activated human endothelial cells with fluorescent bacteria under high-shear-rate conditions revealed 95% attachment of the S aureus by ultralarge von Willebrand factor (ULVWF). Flow experiments with VWF deletion mutants and heparin indicate a contribution of the A-type domains of VWF to bacterial binding. In this context, analyses of different bacterial deletion mutants suggest the involvement of wall teichoic acid but not of staphylococcal protein A. The presence of inactivated platelets and serum increased significantly ULVWF-mediated bacterial adherence. ADAMTS13 (a disintegrin and metalloproteinase with thrombospondin motifs 13) caused a dose-dependent reduction of bacterial binding and a reduced length of ULVWF, but single cocci were still tethered by ULVWF at physiological levels of ADAMTS13. To further prove the role of VWF in vivo, we compared wild-type mice with VWF knockout mice. Binding of fluorescent bacteria was followed in tumor necrosis factor-α-stimulated tissue by intravital microscopy applying the dorsal skinfold chamber model. Compared with wild-type mice (n=6), we found less bacteria in postcapillary (60±6 versus 32±5 bacteria) and collecting venules (48±5 versus 18±4 bacteria; P<0.05) of VWF knockout mice (n=5). - - Conclusions— - - Our data provide the first evidence that ULVWF contributes to the initial pathogenic step of S aureus-induced endocarditis in patients with an apparently intact endothelium. An intervention reducing the ULVWF formation with heparin or ADAMTS13 suggests novel therapeutic options to prevent infective endocarditis.
Gesehen am 31.03.2022